PENDEKATAN PEMEKARAN WILAYAH, PRINSIP DAN FILOSOFINYA UNTUK TANAH PAPUA - Melmambessy, Moses; ACHMADY, LA (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2020)
Regional autonomy has brought impact of the desire to split parts of themselves or in other words, broke away to become the new autonomous region. Regional expansion is not just happening at the provincial level, but also occurred in the district / city level. The number of Regency / City is far more than the number of provincial post-reform 1999. Regional expansion phenomenon was driven by several factors that support among the existing regulations already provide a tremendous opportunity for the proliferation of regional expansion proposals. The procedure is quite easy, and encouraged some of the motives of